Staphylococcus aureus Cell Wall Biosynthesis Modulates Bone Invasion and Osteomyelitis Pathogenesis - Masters, Elysia A.; Muthukrishnan, Gowrishankar; Ho, Lananh; Gill, Ann Lindley; de Mesy Bentley, Karen L.; Galloway, Chad A.; McGrath, James L.; Awad, Hani A.; Gill, Steven R.; Schwarz, Edward M. (Frontiers in Microbiology, 2021)
S. aureus invasion of the osteocyte-lacuno canalicular network (OLCN) is a novel mechanism of bacterial persistence and immune evasion in chronic osteomyelitis. Previous work highlighted S. aureus cell wall transpeptidase, penicillin binding protein 4 (PBP4), and surface adhesin, S. aureus surface protein C (SasC), as critical factors for bacterial deformation and propagation through nanopores in vitro, representative of the confined canaliculi in vivo. Given these findings, we hypothesized that cell wall synthesis machinery and surface adhesins enable durotaxis- and haptotaxis-guided invasion of the OLCN, respectively. Here, we investigated select S. aureus cell wall synthesis mutants (∆pbp3, ∆atl and ∆mreC), and surface adhesin mutants (∆clfA and ∆sasC), for nanopore propagation in vitro and osteomyelitis pathogenesis in vivo. In vitro evaluation in the Microfluidic Silicon-Membrane Canalicular Array (µSiM-CA) showed pbp3, atl, clfA and sasC deletion reduced nanopore propagation. Using a murine model for implant-associated osteomyelitis, S. aureus cell wall synthesis proteins were found to be key modulators of S. aureus osteomyelitis pathogenesis, while surface adhesins had minimal effects. Specifically, deletion of pbp3 and atl decreased septic implant loosening and S. aureus abscess formation in the medullary cavity, while deletion of surface adhesins showed no significant differences. Further, peri-implant osteolysis, osteoclast activity, and RANKL production were decreased following pbp3 deletion. Most notably, transmission electron microscopy (TEM) imaging of infected bone showed that pbp3 was the only gene herein associated with decreased sub-micron invasion of canaliculi in vivo. Together, these results demonstrate that S. aureus cell wall synthesis enzymes are critical for OLCN invasion and osteomyelitis pathogenesis in vivo.